Physicochemical characteristics of Croatian royal jelly - Flanjak, Ivana (Array, 2019)
Due to its high nutritive value, royal jelly usage is increasing, both in human nutrition in native form and as bioactive component in other products (dietary supplements, medicines). The database and regulations on royal jelly characteristics are established in several countries, but not in Croatia. Physicochemical characteristics: moisture, protein content, pH value, total acidity, carbohydrate composition and 10-HDA content in 13 Croatian royal jelly samples were determined with the aim of getting insight to quality of royal jelly produced in Croatia. The obtained results showed that regarding 10-HDA content, one of the most important quality parameter, all samples fulfilled the international standard for royal jelly specifications. Moisture of three samples was higher than prescribed (69.5%, 76.3% and 72.0%, respectively) while one sample had slightly lower protein content than minimum 11% prescribed in international standard. Sucrose content in two royal jelly samples was higher than 3%. Statistically significant correlations were obtained between moisture and protein content, 10-HDA and total acidity as well as between fructose and glucose content. The results of this study will contribute to create the database of Croatian royal jelly physicochemical characteristics and thus help in setting the royal jelly quality criteria at national level.